Improved Mobilized Strength Design Method for Multi-Support Excavation Deformation Analysis - Bingxiong Tu; Meng Han; Jinqing Jia; Zhaoyun Xiao; Lulu Liu (Buildings)
The safe and reliable design of underground spaces ensures the safety of a structure itself and its surroundings. The traditional Mobilized Strength Design (MSD) method for a multi-support excavation deformation analysis ignores the effects of soil parameters and excavation boundary conditions. Therefore, to compensate for the shortcomings of the existing MSD method, this paper proposes an improved mobilized strength design (IMSD) method for a multi-support excavation deformation analysis. The improved incremental deformation mechanism further considers the effect of the soil friction angle, and the effect of excavation depth and the first support on deformation energy are also considered. Further, the excavation calculation process based on the IMSD method is given, and the effects of different calculation parameters on the IMSD solution of excavation deformation are discussed. The results show that the IMSD method can effectively consider the effect of boundary conditions and the excavated process on the excavation deformation. The traditional MSD method underestimates the excavation deformation and surface settlement by an average of 15–23%, while the IMSD solution is more consistent with the measured values. The study results can provide a theoretical reference for the design of multi-support excavation.